Piecing together Ilocano history through manuscript records in Ilocano Diocesan Archives - Jose, Regalado Trota (2001)
The collection of Ilocano diocesan materials from the archives of the Archdiocese in Vigan, the Diocese of Laoag, and the Diocese of San Fernando (La Union) presented here is by no means complete, there being many other materials which still have to be retrieved from the various parishes. Lack of time has prevented a fuller description of most of the documents; the cataloguing is also inconsistent in the use of certain abbreviations. For example, categories in English were used for the archives of Laoag and San Fernando; in the case of Nueva Segovia, which was catalogued a little later, the use of Spanish terms seemed more appropriate. Examination of the materials was made more difficult by the brittleness and extremely dilapidated condition of a great number of them. But the survival of such documents at all is a minor miracle- all of sudden there is the realization that there is yet so much to learn about ourselves and our past (and how this can help us deal with the future). In due time a more complete catalogue of the contents of the archives, it is hoped, will be made available.